IMPACT OF MARKETING STRATEGIES IMPLEMENTED BY THE ORANGE TELECOMMUNICATION COMPANY ON THE OFFERING OF ITS SERVICES BY MOBILE TELEPHONE IN KINDU - LOMBE MULAMBA, (International Journal For Research In Business, Management And Accounting, 2024)
The evaluation of the impact of the marketings strategies impemented by mobile phone telecommunication company in Kindu is main concern of this research. To achieve this, a few indicators were retained and analyzed, namely : marketing costs, turnover, operating profit, operating coefficient and brand coefficient of net operating profit. From the statistical processing of the data analysis of the results, it clearly emerges that the marketing strategies implemented by this company in Kindu have positively inflenced the offer of its services to Kindu during the four years used for this research. And that these have allowed this company to face not only competition, but also to develop its sales.